Organophosphorus Compound Poisoning and Its Outcome: Experience from a Teaching Hospital of Bangladeh (BIRDEM Medical Journal, 2017)
Background: Household and agricultural products containing organophosphorus compound (OPC) pesticides are easily available allowing opportunities for easy source of poisoning throughout the world. Bangladesh is no exception. This study was aimed to find out some epidemiological and demographic profile and immediate outcome of OPC poisoning cases.Methods: This cross-sectional study was done at Rajshahi Medical College Hospital from January to December 2007 and consecutively selected 100 patients with OPC poisoning were studied.Results: Half of the patients belonged to age group 16 25 years, 60% were male, 60% were married, 36% were illiterate and 25% were housewives. Suicidal attempt (85%) was the main intention and the commonest cause was familial disharmony (42%). Gastrointestinal (91%) and pupillary (90%) features were predominant. Most (65%) cases received initial treatment at local hospitals within 30 minutes of ingestion of poison and severity was mild. Forty percent patients required less than 50 ampules of atropine and 75% required 0 3 ampules of pralidoxime. Full recovery was achieved in 82% cases, 8% developed intermediate syndrome and 10% died (6/10, 60% within 24 hours of admission). Hospital stay was